To the question of preparedness of a teacher for professional activities in a polycultural educational environment - S. V. Mazharenko (Вестник Северо-Кавказского федерального университета)
The article outlines the problem of the teacher’s professional readiness in the context of strengthening the multicultural factor in the educational space of the region. The results of an empirical study of the positions of teachers regarding the implementation of their professional tasks in an ethnically heterogeneous educational environment are presented, taking into account the imperative significance of the processes of positive socialization and individualization of students. Identification of some aspects of professional readiness and deficiencies was carried out on the basis of a survey of teaching staff of educational organizations of the Stavropol Territory, whose professional activities take place in a situation of steady growth in the ethnocultural heterogeneity of children’s educational teams.